Symposium 3: Contested disciplinarity in international doctoral supervision - Parchoma, Gale; Keefer, Jeffrey M. (Proceedings of the International Conference on Networked Learning, 2012)
Preliminary results of a grounded-theory informed study of fourteen international doctoral supervisors’ experiences in dealing with interdisciplinary issues in their supervisory practices are reported in this paper. All participants in this study had supervised or were in the process supervising interdisciplinary doctoral theses with interests in the educational research, technology enhanced learning, and/or networked learning. All had some experience with using technologies to support supervision at a distance. Where the full study examined a series of five questions on supervisory experiences, insights, and uses of technology, this paper reports only a subset of data associated with interdisciplinary experiences, insights, and challenges. Doctoral programmes with foci in the fields of educational research, technology enhanced and networked learning often to include academic staff and doctoral candidates from a fairly wide range of originating disciplines. Expanding technological support for part-time, distance, flexible access to doctoral programmes can bring together international groups of tutors and learners. Increasing enrolment and student diversity are sometimes leading to looser ties between supervisory expertise and thesis topics. The field has been described as inherently multi- (Conole & Oliver, 2002), inter- (Parchoma, 2011), and even trans-disciplinary (Becher & Trowler, 2001), thus raising questions on whether these descriptions are substantively different or whether a closer examination of the terms themselves can clarify discussions. We posit an in-progress conceptual framework for examining perspectives on disciplinarity and report supervisory challenges as linked to supporting supervisees to overcome domain knowledge gaps and to develop methodological expertise in this evolving field. We argue that our findings support a view of the field that extends beyond a multidisciplinary mosaic of research on the same area of interest, but from different mono-disciplinary angles to a more cooperative endeavour that involves interdisciplinary boundary crossings. Early findings from this study suggest that efforts to find a shared theoretical underpinning for the field face a series of challenges. However, the coming together of constituent technological, educational, and knowledge domains in international TEL/NL research and practice necessitate collaborative efforts reciprocal interdependence among contributors. Thus the nature of the TEL/NL field provides fertile transdisciplinary ground for represented disciplines to affect and potentially be reoriented by others.